Studi Komparatif Persepsi Tentang Stunting Antara Calon Pengantin Laki-Laki Dan Perempuan di Kecamatan Semarang Utara - Amelia, Marnia; Azinar, Muhammad (Jurnal Kesehatan Masyarakat, 2023)
The problem of stunting is still one of the world’s health problems that has not been resolved to date. This problem is proven by WHO data, as many as 149.2 million children under 5 years worldwide experience stunting (WHO, 2021). In 2021 Indonesia is include in the top 5 countries with thw highest stunting rate of 31.8% (WHO, 2022). The purpose of this study was to determine difference in perceptions between prospective grooms and brides for stunting prevention in North Semarang District. This type of research  is descriptive comparativewith cross sectional research design. The data collection technique was carried out using a total sampling technique with a minimum sample of 49 pairs of prospective brides and 98 respondents registered at the KUA. Data collection was obtained using a questionnaire. Data analysis using pearson association. The results of the study found that there were differences in perceptions with gender, namely in the perceptions of benefits (p=0.003) suggestions for this study are expected for future researchers to conduct further research by deepening or adding variables and using different research methods